2006
DOI: 10.4049/jimmunol.176.3.1848
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Actions of Neuroprotectin D1/Protectin D1 and Its Natural Stereoisomers: Assignments of Dihydroxy-Containing Docosatrienes

Abstract: Protectin D1, neuroprotectin D1 when generated by neural cells, is a member of a new family of bioactive products generated from docosahexaenoic acid. The complete stereochemistry of protectin D1 (10,17S-docosatriene), namely, chirality of the carbon-10 alcohol and geometry of the conjugated triene, required for bioactivity remained to be assigned. To this end, protectin D1/neuroprotectin D1 (PD1) generated by human neutrophils during murine peritonitis and by neural tissues was separated from natural isomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
427
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 415 publications
(440 citation statements)
references
References 48 publications
7
427
0
1
Order By: Relevance
“…Overall, many of the products characterized upon using DPAn-6 or DPAn-3 as substrates were similar to those obtained from DHA, as reported earlier (1,3,5). As expected, the 15-lipoxygenase products were primarily oxygenated at the C-17-position, ultimately producing 17-HDHA, 17-HDPAn-6, and 17-HDPAn-3 from the respective fatty acids.…”
Section: Products Formed Upon Reaction Of Fatty Acids With 5- 12- Asupporting
confidence: 81%
See 2 more Smart Citations
“…Overall, many of the products characterized upon using DPAn-6 or DPAn-3 as substrates were similar to those obtained from DHA, as reported earlier (1,3,5). As expected, the 15-lipoxygenase products were primarily oxygenated at the C-17-position, ultimately producing 17-HDHA, 17-HDPAn-6, and 17-HDPAn-3 from the respective fatty acids.…”
Section: Products Formed Upon Reaction Of Fatty Acids With 5- 12- Asupporting
confidence: 81%
“…The number of peaks, integration, and chemical shifts in both the one-dimensional 1 H and the one-dimensional 13 C spectra were consistent with the molecular formula C 22 H 34 O 3 and were consistent with spectra predicted by Chemdraw and ACDlabs software. The two-dimensional 1 H, 1 H COSY unambiguously showed that hydroxylation was at the 17-position. The protons belonging to C (17) -H-OH centered at 4.12 ppm produced cross-peaks to C (16) -H and C (18) -H but not with protons belonging to C (13) or C (14) .…”
Section: Products Formed Upon Reaction Of Fatty Acids With 5- 12- Amentioning
confidence: 96%
See 1 more Smart Citation
“…Newly identified potent n-3 fatty acid-derived mediators such as the resolvins, including RvE1 and resolvin D3 (RvD3), and protectins, i.e., neuroprotectin D1 (NPD1)͞protectin D1 (PD1), are antiinflammatory (20,21). We assessed both n-6 and n-3 PUFA-derived mediators from colons using liquid chromatography-UV-tandem MS mediator informatics to determine whether the difference in DSS-induced colitis observed between WT and fat-1 mice was associated with these pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The newly identified n-3-derived resolvins and protectins are potent antiinflammatory mediators in various settings, including trinitrobenzene sulfonate colitis and periodontitis (20,21,29,30). These lipid mediators have been shown to decrease formation of inflammatory cytokines such as TNF␣, IL-6, and others (31,32).…”
Section: Discussionmentioning
confidence: 99%